The transcriptional regulator PRDM12 is critical for Pomc expression in the mouse hypothalamus and controlling food intake, adiposity, and body weight - Hael, Clara Ercilia (2020)
Objective: Regulation of food intake and energy balance depends on a group of hypothalamic neurons that release anorexigenic melanocortins encoded by the Pomc gene. Although the physiological importance of central melanocortins is well appreciated, the genetic program that defines the functional identity of melanocortin neurons and assures high levels of hypothalamic Pomc expression is only beginning to be understood. This study assessed whether the transcriptional regulator PRDM12, identified as a highly expressed gene in adult mouse POMC neurons, plays an important role in the identity and function of melanocortin neurons. Methods: We first determined the cellular distribution of PRDM12 in the developing hypothalamus. Then we studied mutant mice with constitutively inactivated Prdm12 to evaluate possible changes in hypothalamic Pomc expression. In addition, we characterized conditional mutant mice specifically lacking Prdm12 in ISL1-positive or POMC neurons during development. Finally, we measured food intake, body weight progression up to 16 weeks of age, adiposity, and glucose tolerance in adult mice lacking Prdm12 selectively from POMC neurons. Results: PRDM12 co-expressed with POMC in mouse hypothalamic neurons from early development to adulthood. Mice lacking Prdm12 displayed greatly reduced Pomc expression in the developing hypothalamus. Selective ablation of Prdm12 from ISL1 neurons prevented hypothalamic Pomc expression. The conditional ablation of Prdm12 limited to POMC neurons greatly reduced Pomc expression in the developing hypothalamus and in adult mice led to increased food intake, adiposity, and obesity. Conclusions: Altogether, our results demonstrate that PRDM12 plays an essential role in the early establishment of hypothalamic melanocortin neuron identity and the maintenance of high expression levels of Pomc. Its absence in adult mice greatly impairs Pomc expression and leads to increased food intake, adiposity, and obesity